Different Neural Correlates of Emotion-Label Words and Emotion-Laden Words: An ERP Study - Zhang, Juan; Wu, Chenggang; Meng, Yaxuan; Yuan, Zhen (Frontiers in Human Neuroscience, 2017)
It is well-documented that both emotion-label words (e.g., sadness, happiness) and emotion-laden words (e.g., death, wedding) can induce emotion activation. However, the neural correlates of emotion-label words and emotion-laden words recognition have not been examined. The present study aimed to compare the underlying neural responses when processing the two kinds of words by employing event-related potential (ERP) measurements. Fifteen Chinese native speakers were asked to perform a lexical decision task in which they should judge whether a two-character compound stimulus was a real word or not. Results showed that (1) emotion-label words and emotion-laden words elicited similar P100 at the posteriors sites, (2) larger N170 was found for emotion-label words than for emotion-laden words at the occipital sites on the right hemisphere, and (3) negative emotion-label words elicited larger Late Positivity Complex (LPC) on the right hemisphere than on the left hemisphere while such effect was not found for emotion-laden words and positive emotion-label words. The results indicate that emotion-label words and emotion-laden words elicit different cortical responses at both early (N170) and late (LPC) stages. In addition, right hemisphere advantage for emotion-label words over emotion-laden words can be observed in certain time windows (i.e., N170 and LPC) while fails to be detected in some other time window (i.e., P100). The implications of the current findings for future emotion research were discussed.